The influence of microencapsulation with a modified chitosan (water soluble) on ß-galactosidase activity - Berta N. Estevinho (2014)
The aim of this work was to investigate the possibility ofproducing microparticles containing b-galactosidase, using a modified chitosan (water soluble) as encapsulating agent. b-galactosidasemicroparticles were prepared by a spray-drying method and werecharacterized in terms of particle size, surface morphology, zetapotential, and stability over a storage period of six months. Microparticles were also analyzed by FTIR spectroscopy and thermogravimetry techniques. Structural analysis of the surface of the particleswas performed by scanning electron microscopy (SEM). SEMresults show that the obtained microparticles have an average diameter smaller than 3.5 lm and a regular shape. The b-galactosidaseactivity decreases when microencapsulated. The parameters Kmand Vmax of the Michaelis-Menten equation were calculated forthe different experimental conditions. The optimal pH ranges from6.4 to 7.2, approximately, depending on the enzyme concentrationin the microcapsule. After six months of storage, the enzyme activitypresents a small decrease, although no significant differences in theappearance, color, and particle size distribution were identified.